Anti-yellowing and anti-embrittlement silk and preparation method thereof
By spraying nano-silicon dioxide suspension on mulberry leaves, it enters the silk, which solves the problem of the silk being easy to yellow and brittle, improves the mechanical properties and UV resistance of the silk, and achieves environmentally friendly and efficient silk modification.
Patent Information
- Application Number
- CN202411828552.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The problem of silk being easily yellowed and brittled affects its aesthetics and service life. The existing research on food production has problems such as toxicity, high cost and low conversion, and lacks silk modification technology for ultraviolet rays.
By spraying nanosilicon dioxide suspension on mulberry leaves and feeding silkworms, the nanosilicon dioxide enters the silk and is combined into the silk, thereby improving the mechanical properties and UV resistance of the silk.
The anti-yellowing and anti-brittlement of silk is achieved, which improves the mechanical properties and ultraviolet resistance of silk, reduces production costs, and is environmentally friendly and efficient.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of silk fiber and its modification, and particularly relates to anti-yellowing and anti-embrittlement silk and a preparation method thereof. Background Art
[0002] Silk is an important natural protein fiber. It is a continuous long fiber formed by the solidification of silk liquid secreted by mature silkworms when they make cocoons. Silk has excellent mechanical properties, good biocompatibility and biodegradability, and is widely used in traditional textile fields as well as modern materials and medical fields. However, silk also has some shortcomings. The main disadvantage of silk fabrics is that they are prone to yellowing and brittleness, which greatly affects the appearance and use of silk fabrics. In order to improve the defects of silk, enhance the existing properties of silk or give silk special properties, and further expand the application field of silk, a large number of studies are devoted to silk modification and fabric functional finishing.
[0003] Commonly used methods for silk modification include physical methods, chemical methods, molecular biology methods, and feeding silkworms. Among them, feeding silkworms is simple, environmentally friendly, and highly operable. It is the most direct and effective method for mass production of modified silk. Feeding silkworms has the advantages of being simple, efficient, environmentally friendly, and conducive to large-scale production. It can modify the properties of silk at the source. Modifying silk and giving it new functions through this method can expand the application field of silk and is expected to promote the development of the silk industry. However, existing research on feeding still has problems such as toxicity of the added food, high cost, and low conversion rate of the added food, and it focuses more on improving mechanical properties. There has been no report on research on anti-yellowing and anti-brittle UV silk. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a yellowing and brittleness-proof silk and a preparation method thereof. The production process is simple and easy, the overall cost is low, and the cycle is short. The mechanical properties of the obtained silk are significantly improved, and the performance of the silk can be maintained under high ultraviolet radiation intensity, effectively preventing the silk from yellowing and brittleness.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] The present invention provides anti-yellowing and anti-brittle silk and a preparation method thereof, wherein a nano-silicon dioxide suspension is uniformly sprayed on mulberry leaves and the leaves are fed to silkworms, the silkworms absorb the nano-silicon dioxide and enter the silk glands, and finally the nano-silicon dioxide is incorporated into the silk during the silkworm spinning and cocooning process, thereby obtaining the modified anti-yellowing and anti-brittle silk;
[0007] The nano silicon dioxide is configured into a uniform suspension with a mass concentration gradient of 0.5% to 4%.
[0008] A yellowing and embrittlement-resistant silk and a preparation method thereof, comprising the following steps:
[0009] Step 1: Feeding silkworms with ordinary mulberry leaves from the first to fourth instars;
[0010] Step 2, starting from the second day of the fifth instar, different groups of silkworms were fed with different food. The control group was fed with ordinary mulberry leaves, and the silkworms in different concentration groups were fed with mulberry leaves sprayed with corresponding concentrations of nano-silicon dioxide. The concentration of the nano-silicon dioxide suspension was 0.5% to 4%, and the silkworms absorbed the nano-silicon dioxide into the silk gland. The fifth instar is the main stage for silkworms to absorb nutrients. The nutrients absorbed during this period are mainly used for the synthesis of silk substances. In addition, the silkworms have grown more mature at this stage and are not easy to die. Therefore, the fifth instar was selected for feeding in this experiment.
[0011] Step 3, feeding the silkworms with mulberry leaves sprayed with nano-silicon dioxide until the seventh day of the fifth instar, the nano-silicon dioxide that enters the silk gland will eventually be incorporated into the silk during the spinning process until the cocoon is formed on the upper cluster, thus obtaining the anti-yellowing and anti-brittleness silk.
[0012] Furthermore, in step 1, the nano-silicon dioxide suspension is sprayed on the mulberry leaves, and the specific process includes the following steps:
[0013] (1) Weighing a certain amount of nano-silicon dioxide and adding it to deionized water, dispersing it by ultrasound for 30 minutes, and preparing a suspension with a mass concentration gradient of 0.5% to 4%;
[0014] (2) The three suspensions were placed in small spray bottles respectively, and sprayed evenly on the mulberry leaves. After drying at room temperature, they were used as supplementary feed.
[0015] The anti-yellowing and anti-brittleness silk and its preparation method as described above, the silkworms should be selected from silkworms of equal size and good growth condition, the silkworms are reared at a temperature of 25+2°C and a relative humidity of 75%, mulberry is fed regularly every day during the feeding period, and silkworm excrement is cleaned in time until the seventh day of the fifth instar, when the silkworms stop eating and the front half of the body becomes transparent, that is, they start to spin silk and make cocoons on the cocoon. After the silkworms make cocoons, the cocoons are collected and dried at 110°C for 3 hours.
[0016] Furthermore, the specific process of removing sericin includes the following steps:
[0017] (1) Boil the cocoons in 70°C water for 15 minutes, and peel off the outer cocoon skin after it softens;
[0018] (2) Found the cocoon head and wound it on a hand-cranked silk reeling machine to obtain silk fibers, put these fibers into a 100°C Na2CO3 solution and boil them for 30 minutes to remove the sericin, then rinse the silk with deionized water three times to remove the residual Na2CO3 solution and sericin on the surface until the degumming is completed;
[0019] (3) The degummed silk is placed in a cool place to dry naturally to obtain yellowing and brittleness-resistant silk.
[0020] A yellowing and brittleness-resistant silk obtained by any one of the above methods.
[0021] Compared with the prior art, the present invention has the following beneficial technical effects:
[0022] The present invention sprays a certain mass concentration of amphiphilic nano-silicon dioxide suspension on ordinary mulberry leaves to feed silkworms, and the nano-silicon dioxide enters the silk through the silkworms' own absorption. Nano-silicon dioxide is non-toxic and has a small particle size, so that it can be ingested and absorbed by silkworms in large quantities. In addition, there are a large number of hydroxyl groups on the surface of nano-silicon dioxide, which may form hydrogen bonds with silk protein molecules. This interaction can promote its retention in the silkworm body, so that it appears in large quantities in silk; and the existence of hydrogen bonds between nano-silicon dioxide and silk protein molecular chains can limit the movement of its molecular chains, thereby hindering the transformation of silk protein conformation from random curling to β-folded structure, further leading to a decrease in crystallinity. Thus, nano-silicon dioxide, as a network node like β-folded microcrystals, can increase the density of the network, thereby more effectively dispersing external forces and improving its mechanical properties.
[0023] One of the main drawbacks of silk fabrics is that they turn yellow easily, which is related to ultraviolet rays. When exposed to ultraviolet rays for a long time, ultraviolet rays react with certain amino acids in silk, such as glycine and serine, to generate a conjugated system with color development, which causes the silk to turn yellow. In addition, ultraviolet rays accelerate the aging of silk fabrics and reduce their mechanical properties. Nano-silica can effectively reflect ultraviolet rays. After adding nano-silica, these nanoparticles enter the silk fibers in large quantities, thereby improving the anti-ultraviolet performance of silk fibers.
[0024] The anti-yellowing and anti-embrittlement silk products produced by the present invention show improved mechanical properties and excellent UV resistance without changing the original excellent quality of the silk. This modified silk may be more widely used in the future. The method has the advantages of environmental protection, low cost, high efficiency, etc., and provides a broader commercial prospect for sericulture and silk utilization. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:
[0026] Figure 1 The growth conditions of silkworms in each example, including: (a) photos of five-year-old silkworms in the control group and examples 1, 2, and 3; (b) silkworm weight; (c) average silkworm weight growth rate;
[0027] Figure 2is the cocoon quality analysis of each example, including: (a) photos of cocoons of the control group and examples 1, 2, and 3, (b) dry weight of cocoons, and (c) shape of cocoons;
[0028] Figure 3 is the SEM photograph of the appearance of the silk of each example;
[0029] Figure 4 is the measurement result of the silk diameter of each example silk;
[0030] Figure 5 is the silicon content in the silk of each example;
[0031] Figure 6 is the stress-strain curve of silk fiber in each example;
[0032] Figure 7 The figure shows the changes in mechanical properties of the silk of each example after being treated with ultraviolet rays of different energies, including (a) the stress of the silk of each example after being treated with ultraviolet rays of different irradiation energies, and (b) the strain of the silk of each example after being treated with ultraviolet rays of different irradiation energies. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with specific implementation methods. It should be understood that the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Before the experiment, the silkworms were first selected, and hundreds of silkworms of similar size and good growth conditions were selected. Then the silkworms were divided into groups that were fed with 0.5% to 4% nano-silicon dioxide.
[0035] Weigh a certain amount of nano-silicon dioxide and add it to deionized water, and prepare it into a uniform suspension with a mass concentration gradient of 0.5% to 4% by ultrasonic dispersion (30 minutes). The three suspensions were respectively placed in small spray bottles, sprayed evenly on mulberry leaves, and dried at room temperature as spare feed.
[0036] The fifth instar is the main stage for silkworms to absorb nutrients. The nutrients absorbed during this period are mainly used for the synthesis of silk materials. In this stage, silkworms have grown more mature and are not easy to die. Therefore, in this experiment, different groups of silkworms were fed with different feedings from the second day of the fifth instar. The control group was fed with ordinary mulberry leaves, and the different concentration groups were fed with mulberry leaves sprayed with corresponding concentrations of nano-silicon dioxide. The silkworm breeding temperature was 25±2℃ and the relative humidity was 75%. During the feeding period, mulberry leaves were given regularly every day, and the silkworm feces were cleaned in time until the seventh day of the fifth instar, when the silkworms stopped eating and the front half of their bodies became transparent, that is, they began to spin silk and make cocoons on the cocoon. After the silkworms made cocoons, the cocoons were collected and dried at 110℃ for 3h, and then dried and stored for the next test.
[0037] Boil the cocoons in 70℃ water for 15 minutes, peel off the outer cocoon skin after it softens, and then find the cocoon head by threading, wrap it around the ruler (hand-cranked silk reeling machine) and twist it to get silk fiber. The ruler is divided into 100 turns (100 meters), and 300-400 turns of silk fiber are taken for degumming. These fibers are placed in 100℃ Na2CO3 solution and boiled for 30 minutes to remove sericin. Then, the silk is rinsed three times with deionized water to remove the residual Na2CO3 solution and sericin on the surface. Finally, the two merged silk fibers are separated to get single silk fibers for subsequent testing.
[0038] Example 1
[0039] In this example, silkworms were fed with mulberry leaves sprayed with a nano-silicon dioxide suspension having a mass concentration of 2%.
[0040] (1) Select hundreds of silkworms of similar size and good growth condition. Feed the silkworms with ordinary mulberry leaves from the first to fourth instars, and feed them with mulberry leaves sprayed with a 2% nano-silicon dioxide suspension from the second day of the fifth instar. The silkworm rearing temperature is 25±2℃ and the relative humidity is 75%. During the feeding period, mulberry leaves are given regularly every day, and the silkworm feces are cleaned in time until the seventh day of the fifth instar, when the silkworms stop eating and the front half of their bodies become transparent, that is, they start to spin silk and make cocoons on the cocoon. After the silkworms make cocoons, collect the cocoons and bake them at 110℃ for 3h, and then dry them for the next test.
[0041] (2) Spraying a nano-silicon dioxide suspension on mulberry leaves. The specific process includes the following steps: weighing a certain amount of nano-silicon dioxide and adding it to deionized water. After ultrasonic dispersion for 30 minutes, the suspension is prepared into a suspension with a mass concentration gradient of 2%; the suspension is placed in small spray bottles, sprayed evenly on the mulberry leaves, and dried at room temperature as a spare feed.
[0042] (3) Boil the cocoons in 70℃ water for 15 minutes, peel off the outer cocoon skin after it softens, and then find the cocoon head by threading, wrap it around a measuring machine (hand-cranked silk reeling machine) and twist it to obtain silk fibers. The measuring machine is divided into 100 turns (100 meters), and 300-400 turns of silk fibers are taken for degumming. These fibers are placed in a 100℃ Na2CO3 solution and boiled for 30 minutes to remove sericin. Then, the silk is rinsed three times with deionized water to remove the residual Na2CO3 solution and sericin on the surface. Finally, the two merged silk fibers are separated to obtain single silk fibers for subsequent testing.
[0043] (4) Silkworm growth record and cocoon quality measurement. Starting from the first day of feeding, the weight of each group of silkworms was weighed at the same time every day to monitor the weight changes of silkworms and calculate their survival rate. Twenty cocoons from each group were randomly selected for weight and cocoon shape (length and width) measurement to compare and analyze the effect of feeding nano-silica on cocoon quality.
[0044] (5) Observation of the appearance and morphology of modified silk. The diameter of silk was measured by polarizing microscope. 20 silk samples were taken in each group. Each silk sample was 1 cm long. The diameter data of three positions of each sample were measured. A total of 60 data were obtained in each group. The average value was taken as the diameter of the silk in this group. The appearance and morphology of silk were observed by SEM. The length of the silk sample was 1 cm. The electron acceleration voltage was set to 5 kV.
[0045] (6) Test of silicon content in modified silk. The silicon content in modified silk was tested using an inductively coupled plasma mass spectrometer (ICP-MS), with the nebulizer chamber temperature at 2°C and the radio frequency power at 1500W.
[0046] (7) Test of mechanical properties of modified silk. The mechanical properties of degummed silk were tested using a tensile testing machine. The test environment was a constant temperature and humidity laboratory with a temperature of 22.3°C and a relative humidity of 50%. The tensile rate was 1 mm / min. The pressure of the pressure measuring element was set to 0.5 N. 30 sets of data were obtained for each test, and the mean and standard deviation of stress and strain were calculated. Sample preparation method: First, a hollow rectangular cardboard frame with a width of 1 cm was made. The degummed silk was fixed to the cardboard frame with tape. After the upper and lower chucks were fixed, the cardboard was cut and stretched.
[0047] (8) Test of the anti-ultraviolet performance of modified silk. Prepare silk samples according to the sample preparation method of tensile test, place the samples under ultraviolet light for irradiation, and irradiate them at 398 and 796 MJ / m 2 After the treatment of ultraviolet radiation, the control group and the food supplement group were subjected to tensile tests respectively, and the test method was the same as the mechanical property test mentioned above. The anti-ultraviolet effect was measured by comparing the degree of loss of mechanical properties of silk.
[0048] Example 2
[0049] In this example, silkworms were fed with mulberry leaves sprayed with a nano-silicon dioxide suspension having a mass concentration of 3%.
[0050] (1) Select hundreds of silkworms of similar size and good growth condition. Feed the silkworms with ordinary mulberry leaves from the first to fourth instars, and feed them with mulberry leaves sprayed with a 3% nano-silicon dioxide suspension from the second day of the fifth instar. The silkworm rearing temperature is 25±2℃ and the relative humidity is 75%. During the feeding period, mulberry leaves are added regularly every day, and the silkworm feces are cleaned in time until the seventh day of the fifth instar, when the silkworms stop eating and the front half of their bodies become transparent, that is, they start to spin silk and make cocoons on the cocoon. After the silkworms make cocoons, collect the cocoons and bake them at 110℃ for 3h, and then dry them for the next test.
[0051] (2) Spraying a nano-silicon dioxide suspension on mulberry leaves. The specific process includes the following steps: weighing a certain amount of nano-silicon dioxide and adding it to deionized water. After ultrasonic dispersion for 30 minutes, the suspension is prepared into a 3% mass concentration gradient suspension; the suspension is respectively placed in small spray bottles, sprayed evenly on the mulberry leaves, and dried at room temperature as a spare feed.
[0052] (3) Boil the cocoons in 70℃ water for 15 minutes, peel off the outer cocoon skin after it softens, and then find the cocoon head by threading, wrap it around a measuring machine (hand-cranked silk reeling machine) and twist it to obtain silk fibers. The measuring machine is divided into 100 turns (100 meters), and 300-400 turns of silk fibers are taken for degumming. These fibers are placed in a 100℃ Na2CO3 solution and boiled for 30 minutes to remove sericin. Then, the silk is rinsed three times with deionized water to remove the residual Na2CO3 solution and sericin on the surface. Finally, the two merged silk fibers are separated to obtain single silk fibers for subsequent testing.
[0053] (4) Silkworm growth record and cocoon quality measurement. Starting from the first day of feeding, the weight of each group of silkworms was weighed at the same time every day to monitor the weight changes of silkworms and calculate their survival rate. Twenty cocoons from each group were randomly selected for weight and cocoon shape (length and width) measurement to compare and analyze the effect of feeding nano-silica on cocoon quality.
[0054] (5) Observation of the appearance and morphology of modified silk. The diameter of silk was measured by polarizing microscope. 20 silk samples were taken in each group. Each silk sample was 1 cm long. The diameter data of three positions of each sample were measured. A total of 60 data were obtained in each group. The average value was taken as the diameter of the silk in this group. The appearance and morphology of silk were observed by SEM. The length of the silk sample was 1 cm. The electron acceleration voltage was set to 5 kV.
[0055] (6) Test of silicon content in modified silk. The silicon content in modified silk was tested using an inductively coupled plasma mass spectrometer (ICP-MS), with the nebulizer chamber temperature at 2°C and the radio frequency power at 1500W.
[0056] (7) Test of mechanical properties of modified silk. The mechanical properties of degummed silk were tested using a tensile testing machine. The test environment was a constant temperature and humidity laboratory with a temperature of 22.3°C and a relative humidity of 50%. The tensile rate was 1 mm / min. The pressure of the pressure measuring element was set to 0.5 N. 30 sets of data were obtained for each test, and the mean and standard deviation of stress and strain were calculated. Sample preparation method: First, a hollow rectangular cardboard frame with a width of 1 cm was made. The degummed silk was fixed to the cardboard frame with tape. After the upper and lower chucks were fixed, the cardboard was cut and stretched.
[0057] (8) Test of the anti-ultraviolet performance of modified silk. Prepare silk samples according to the sample preparation method of tensile test, place the samples under ultraviolet light for irradiation, and irradiate them at 398 and 796 MJ / m 2 After the treatment of ultraviolet radiation, the control group and the food supplement group were subjected to tensile tests respectively, and the test method was the same as the mechanical property test mentioned above. The anti-ultraviolet effect was measured by comparing the degree of loss of mechanical properties of silk.
[0058] Example 3
[0059] In this example, silkworms were fed with mulberry leaves sprayed with a nano-silicon dioxide suspension having a mass concentration of 4%.
[0060] (1) Select hundreds of silkworms of similar size and good growth condition. Feed the silkworms with ordinary mulberry leaves from the first to fourth instars, and feed them with mulberry leaves sprayed with a nano-silicon dioxide suspension with a mass concentration of 4% from the second day of the fifth instar. The silkworm rearing temperature is 25±2℃ and the relative humidity is 75%. During the feeding period, mulberry leaves are given regularly every day, and the silkworm feces are cleaned in time until the seventh day of the fifth instar, when the silkworms stop eating and the front half of their bodies become transparent, that is, they start to spin silk and make cocoons on the cocoon. After the silkworms make cocoons, collect the cocoons and bake them at 110℃ for 3h, and then dry them for the next test.
[0061] (2) Spraying a nano-silicon dioxide suspension on mulberry leaves. The specific process includes the following steps: weighing a certain amount of nano-silicon dioxide and adding it to deionized water. After ultrasonic dispersion for 30 minutes, the suspension is prepared into a suspension with a mass concentration gradient of 4%; the suspension is respectively placed in small spray bottles, sprayed evenly on the mulberry leaves, and dried at room temperature as a spare feed.
[0062] (3) Boil the cocoons in 70℃ water for 15 minutes, peel off the outer cocoon skin after it softens, and then find the cocoon head by threading, wrap it around a measuring machine (hand-cranked silk reeling machine) and twist it to obtain silk fibers. The measuring machine is divided into 100 turns (100 meters), and 300-400 turns of silk fibers are taken for degumming. These fibers are placed in a 100℃ Na2CO3 solution and boiled for 30 minutes to remove sericin. Then, the silk is rinsed three times with deionized water to remove the residual Na2CO3 solution and sericin on the surface. Finally, the two merged silk fibers are separated to obtain single silk fibers for subsequent testing.
[0063] (4) Silkworm growth record and cocoon quality measurement. Starting from the first day of feeding, the weight of each group of silkworms was weighed at the same time every day to monitor the weight changes of silkworms and calculate their survival rate. Twenty cocoons from each group were randomly selected for weight and cocoon shape (length and width) measurement to compare and analyze the effect of feeding nano-silica on cocoon quality.
[0064] (5) Observation of the appearance and morphology of modified silk. The diameter of silk was measured by polarizing microscope. 20 silk samples were taken in each group. Each silk sample was 1 cm long. The diameter data of three positions of each sample were measured. A total of 60 data were obtained in each group. The average value was taken as the diameter of the silk in this group. The appearance and morphology of silk were observed by SEM. The length of the silk sample was 1 cm. The electron acceleration voltage was set to 5 kV.
[0065] (6) Test of silicon content in modified silk. The silicon content in modified silk was tested using an inductively coupled plasma mass spectrometer (ICP-MS), with the nebulizer chamber temperature at 2°C and the radio frequency power at 1500W.
[0066] (7) Test of mechanical properties of modified silk. The mechanical properties of degummed silk were tested using a tensile testing machine. The test environment was a constant temperature and humidity laboratory with a temperature of 22.3°C and a relative humidity of 50%. The tensile rate was 1 mm / min. The pressure of the pressure measuring element was set to 0.5 N. 30 sets of data were obtained for each test, and the mean and standard deviation of stress and strain were calculated. Sample preparation method: First, a hollow rectangular cardboard frame with a width of 1 cm was made. The degummed silk was fixed to the cardboard frame with tape. After the upper and lower chucks were fixed, the cardboard was cut and stretched.
[0067] (8) Test of the anti-ultraviolet performance of modified silk. Prepare silk samples according to the sample preparation method of tensile test, place the samples under ultraviolet light for irradiation, and irradiate them at 398 and 796 MJ / m 2 After the treatment of ultraviolet radiation, the control group and the food supplement group were subjected to tensile tests respectively, and the test method was the same as the mechanical property test mentioned above. The anti-ultraviolet effect was measured by comparing the degree of loss of mechanical properties of silk.
[0068] Experimental Results
[0069] The growth conditions of silkworms in each example are as follows Figure 1 As shown. Figure 1 (ac), as the concentration of nano-silicon dioxide increases, the feeding group still shows no negative impact on the growth of silkworms. They are in good health, with a weight growth trend consistent with the control group, and an average weight growth rate comparable to that of the control group. The above results show that nano-silicon dioxide is a relatively mild feeding substance, and its concentration of 4% still does not affect the normal growth and development of silkworms.
[0070] The cocoon quality analysis of each example is as follows Figure 2 As shown. Figure 2 (a) There is no difference in the surface morphology and color between the feeding group and the control group. The cocoons are long oval and white. Figure 2 (b) It can be seen that the cocoon weights of Example 1, Example 2, and Example 3 are all lower than those of the control group, with the cocoon weight of Example 1 decreasing by 0.06 g, and the cocoon weights of Examples 2 and 3 decreasing by 0.19 g. Figure 2 (c) After feeding with nano-silicon dioxide, the cocoons of Example 1, Example 2, and Example 3 were longer and wider than those of the control group, and the cocoon shape changed to be slightly slender. The above results show that feeding with nano-silicon dioxide has a certain effect on the cocoon quality of silkworms, and is related to the concentration of silicon dioxide. As the concentration increases, the weight of the cocoons decreases, and the cocoon shape tends to change to a slender shape.
[0071] The SEM photos of the appearance of the silk of each example are as follows: Figure 3 As shown in the figure, the surface of the silk fiber modified by nano-silicon dioxide addition is smooth, and there is no difference in appearance with the silk of the control group. The smooth surface is conducive to maintaining the luster of silk.
[0072] The measurement results of the silk diameters of the silkworms in each example are as follows: Figure 4 As shown in the figure, as the concentration of nano-silicon dioxide increases, the diameter of silk slightly decreases, but there is no corresponding relationship between the diameter of silk and the concentration of nano-silicon dioxide. This shows that nano-silicon dioxide may have a certain effect on the secretion and synthesis of silk protein, but the effect is small.
[0073] The silicon content in the silk of each example is as follows Figure 5 As shown. In order to determine whether nano-silicon dioxide is successfully added to silk fibers, the ICP-MS method is used to determine the silicon content in silk fibers. As can be seen from the figure, with the increase of nano-silicon dioxide concentration, the silicon content in silk fibers gradually increases. In particular, the silk with 4% nano-silicon dioxide added in Example 3 has a silicon content of 869.70 mg / kg.
[0074] The stress-strain curves of the silk fibers in each example are shown in Figure 6As shown, the stress-strain values and changes of silk fibers in each example are shown in Table 1. As the concentration of nano-silicon dioxide added to the food increases, the mechanical properties of silk are also improved. The breaking stress of Example 1 is increased to 468.38MPa, which is 18.28% higher than that of the control group. However, there is no absolute positive correlation between the increase in breaking stress and the increase in silicon content. The breaking stress of silk in Example 2 and Example 3 are 426.32MPa and 429.70MPa, respectively, which are 7.66% and 8.50% higher, respectively. It can be found that an appropriate amount of nano-silicon dioxide particles helps to enhance the mechanical properties of silk.
[0075] Table 1 Stress-strain values and changes of silk fibers in each example
[0076]
[0077] The mechanical properties of silk in each example after being treated with ultraviolet rays of different energies are shown in the following figure. Figure 7 As shown. At 398 and 796 MJ / m 2 Under ultraviolet irradiation of 398 MJ / m 2 Under ultraviolet irradiation, the stress did not decrease significantly, and the strain only decreased by 14.08%, which was much lower than that of the control group. 2 After ultraviolet irradiation (equivalent to continuous exposure to strong sunlight for 78 days), the stress and strain decreased by 25.32% and 48.38%, respectively, which were still lower than those of the control group. These results show that nano-silica-modified silk fibers have good UV resistance, can protect silk from being damaged by ultraviolet irradiation, maintain its excellent mechanical properties, and even delay the yellowing of silk fabrics.
Claims
1. A yellowing and embrittlement-resistant silk and a preparation method thereof, characterized in that: Nano-silicon dioxide suspension is evenly sprayed on mulberry leaves and fed to silkworms. The silkworms absorb the nano-silicon dioxide into the silk glands and finally incorporate it into the silk during the silkworm spinning and cocooning process, thus obtaining anti-yellowing and anti-brittleness silk. The nano silicon dioxide is configured into a uniform suspension with a mass concentration gradient of 0.5% to 4%. Specifically, silkworms are fed with ordinary mulberry leaves from the first to fourth instars, and from the second day of the fifth instar, they are fed with mulberry leaves sprayed with nano-silicon dioxide suspensions of different concentrations until the silkworms form cocoons. Spraying nano-silicon dioxide suspension on mulberry leaves, the specific process includes the following steps: (1) A certain amount of nano-silicon dioxide was weighed and added to deionized water. After ultrasonic dispersion for 30 minutes, a uniform suspension with a mass concentration gradient of 0.5% to 4% was prepared. (2) The three suspensions were placed in small spray bottles respectively, and sprayed evenly on the mulberry leaves. After drying at room temperature, they were used as spare feed.
2. The anti-yellowing and anti-embrittlement silk and the preparation method thereof according to claim 1, characterized in that: The silkworms should be selected from silkworms of comparable size and in good growth condition. The silkworm rearing temperature is 25±2°C and the relative humidity is 75%. After the silkworms have cocooned, the cocoons are collected and dried at 110°C for 3 h.
3. An anti-yellowing and anti-brittleness silk as described in any one of claims 1-2 and an anti-yellowing and anti-brittleness silk obtained by the preparation method thereof.
4. The anti-yellowing and anti-embrittlement silk according to claim 3, characterized in that: The specific process of removing sericin includes the following steps: (1) Boil the cocoons in 70°C water for 15 minutes, and peel off the outer cocoon skin after it softens; (2) Find the cocoon head and wind it on a hand-cranked silk reeling machine to obtain silk fibers, put these fibers into a 100°C Na2CO3 solution and boil them for 30 minutes to remove sericin, then rinse the silk with deionized water three times to remove the residual Na2CO3 solution and sericin on the surface until degumming is completed; (3) Place the degummed silk in a cool place to air dry naturally to obtain silk that is anti-yellowing and anti-brittleness.
Citation Information
Patent Citations
Method for preparing mulberry silk containing nanometer TiO2
CN103952774A
Nano-zinc oxide feeding silkworm rearing method for manufacturing high-performance silk and product thereof
CN104872082A
Nano-titanium dioxide-feeding silkworm rearing method for preparing high-performance silk and product prepared by nano-titanium dioxide-feeding silkworm rearing method
CN104878468A
Preparation method of nano-reinforced functional flat silk composite material
CN114128681A